Successful mental health promotion with men: the evidence from 'tacit knowledge'. (19th August 2016) - Robertson, Steve; Gough, Brendan; Hanna, Esmée; Raine, Gary; Robinson, Mark; Seims, Amanda; White, Alan
Abstract: There remains significant concern about men's mental health, particularly in terms of personal and societal barriers to help-seeking, negative coping mechanisms and high suicide rates. This article presents findings from a multi-phase study looking at 'what works' in mental health promotion for men. Work here reports the collection and analysis of the tacit knowledge of those working within mental health promotion interventions for men. A 'multiple hub and spoke' approach was used to assist data collection. Thirteen key players, active in the men's mental health field, half from the UK and half beyond, formed an Investigative Network collecting data, mainly through interviews, from wider geographical and professional community contexts where they had networks. The focus of data collection was on 'what works' in mental health promotion for men. Data was analysed using thematic analysis techniques. Findings suggest that settings which created safe male spaces acted to promote trust, reduce stigma and normalize men's engagement in interventions. Embedding interventions within the communities of men being engaged, fully involving these men, and holding 'male-positive' values engendered familiarity and consolidated trust. Using 'male-sensitive' language and activity-based approaches allowed for positive expressions of emotions, facilitated social engagement, and provided a base for open communication. Appropriate partnerships were also seen as a necessary requirement for success and as crucial for maximizing intervention impact. The importance of gender and 'masculinity' was apparent throughout these findings and taking time to understand gender could facilitate positive ways of working alongside men, increasing levels of engagement and successful outcomes.